Design and Simulation of Multiple Coil Model for Wireless Power Transmission System - Duan Zhao; Enjied Ding; Yanjun Hu; Zhifeng Sun (Institute of Advanced Engineering and Science, 2014)
In Wireless Power Transfer (WPT) systems the proportion of energy received by the load is critical and the efficiency is the more significant parameter. WPT systems use resonant inductive coupling, where it is the near field wireless transmission of electrical energy between two coils that are highly resonant at the same frequency. This paper aims to propose a design of an optimal two dimensional (2D) structure of transmitter and receiver. Multiple overlapping coils structures in the transmitter side are proposed, in order to achieve higher efficiency than the typical single coil transmitter. Simulation results showed that the axial component of magnetic induction resulted from the overlapping coils structure has preferable homogeneous distribution. The proposed system achieved an efficiency value of 90 % for a receiver placed 20 cm away from a 4 coils transmitter comparing to an efficiency value of 75% for the same distance using a single coil transmitter. DOI : http://dx.doi.org/10.11591/telkomnika.v12i6.5119